What is the general solution of the differential equation ? #e^(x^3) (3x^2 y- x^2) dx + e^(x^3) dy =0 #

Answer 1

# y = Ce^(-x^3) + 1/3#

#e^(x^3) (3x^2 y- x^2) dx + e^(x^3) dy =0 # ..... [A]#

Assume we have:

# M(x,y) \ dx = N(x,y) \ dy #
Then the DE is exact if #M_y-N_x=0#
# M = e^(x^3) (3x^2 y- x^2) => M_y = 3x^2e^(x^3) # # N = e^(x^3) => N_x = 3x^2e^(x^3) #
# M_y - N_x = 0 => # an exact DE

Next, our resolution is provided by:

#f_x = M# and #f_y = N# and
Consider #f_x = M => (partial f)/(partial x) = e^(x^3) (3x^2 y- x^2) #
# :. f = int \ x^2e^(x^3) (3y- 1) \ partial x# # \ \ \ \ \ \ \ = 1/3e^(x^3) (3y- 1) # # \ \ \ \ \ \ \ = e^(x^3) y- 1/3e^(x^3) #
Consider #f_y = N => (partial f)/(partial y) = e^(x^3) #
# :. f = int \ e^(x^3) \ partial y# # \ \ \ \ \ \ \ = e^(x^3) y #

The general solution can be formed by combining the elements of both integrals that are common:

# f(x,y) = e^(x^3) y- 1/3e^(x^3) = C #

We now rearrange in order to create an implicit solution.

# e^(x^3) y = C + 1/3e^(x^3)# # :. y = Ce^(-x^3) + 1/3#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the general solution of the given differential equation (e^{x^3}(3x^2y - x^2)dx + e^{x^3}dy = 0), we can separate the variables and integrate.

First, rewrite the equation as (e^{x^3}(3x^2y - x^2)dx = - e^{x^3}dy).

Divide both sides by (e^{x^3}) to isolate (dy), yielding (\frac{3x^2y - x^2}{e^{x^3}}dx = -dy).

Now, integrate both sides with respect to their respective variables. On the left side, integrate with respect to (x), and on the right side, integrate with respect to (y).

This yields (\int \frac{3x^2y - x^2}{e^{x^3}}dx = -\int dy).

Solve the left integral, which might involve a substitution or another integration technique. After finding the antiderivative, set it equal to (-y + C), where (C) is the constant of integration.

This gives the general solution to the differential equation.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7